ALAT UNTUK MENGHITUNG INDEKS MASSA TUBUH (BODY MASS INDEX = BMI) - , AWAL BAYU NIRWIWORO, Ir. Suyoto. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Shortage and excess nutrients in adults is an important issue, it could cause risk certain diseases, affected work productivity and the body shape. Because of that monitoring and evaluating nutrition needs to be a sustainable basis. One way is to maintain an ideal weight or normal. An ideal weight adult can be known based on body mass index (BMI). BMI is a device to find nutritional status a person who is related to weaknesses and strengths weight. BMI using two values that are measured the weight and height. Measuring Instrument body mass index (BMI) with a microcontroller that reads AT mega 16 will make it easier to determine the BMI. This device using two sensors there are ultrasonic sensor (Ping Parallax) to measure height of the body and potentiometer to measure body weight. This measurement result will be processed by a microcontroller that reads AT mega 16 and in view in LCD so users can easily see the value BMI.